Impurity, Moral Substantiality, and Social Control: A Gender Perspective - Alice Van den Bogaert (Religions)
The notion of impurity is identified in numerous belief systems, ranging from certain religions to nationalisms. Understanding its nature and functioning beyond its concrete objects is therefore a fundamental anthropological question. This work is grounded in anthropology, though it may be of interest to scholars from other disciplines. Impurity has been highlighted by numerous authors in ethnographic and theoretical texts, but a comparison of these various works indicates a lack of theoretical development. We will therefore begin by presenting the various explanations attributed to it, before proposing that the notion of impurity is primarily a knowledge of natural laws causing illness, death, and misfortune, based on the observation of contagion and implying an ontology of moral substantiality. I propose this concept to designate an ontology in which everything is a substance (bodily fluids and food, but also glances, words, and thoughts) and at the same time a moral value, without distinguishing between materiality and symbolism, a proposal inspired by McKim Marriott’s substance-codes (1976). This knowledge has then become a tool of social control, aiming to protect reproduction (social, cosmic, and ontological), through its effective language combining a somatopsychological aspect (disgust reaction) and social rejection.